Temporal correlation between the optical and γ -ray flux variations in the blazar 3C 454.3 - Bhoomika Rajput; C. S. Stalin; S. Sahayanathan; Suvendu Rakshit; Amit Kumar Mandal (OXFORD UNIV PRESS, 2022)
Blazars show optical and γ -ray flux variations that are generally correlated, although there are exceptions. Here we present anomalous behaviour seen in the blazar 3C 454.3 based on an analysis of quasi-simultaneous data at optical, ultraviolet, X-ray, and γ -ray energies, spanning about 9 yr from 2008 August to 2017 February.We have identified four time intervals (epochs), A, B, D, and E, when the source showed large-amplitude optical flares. In epochs A and B the optical and γ -ray flares are correlated, while in D and E corresponding flares in γ -rays are weak or absent. In epoch B the degree of optical polarization strongly correlates with changes in optical flux during a short-duration optical flare superimposed on one of long duration. In epoch E the optical flux and degree of polarization are anticorrelated during both the rising and declining phases of the optical flare. We carried out broad-band spectral energy distribution (SED) modelling of the source for the flaring epochs A,B, D, and E, and a quiescent epoch, C. Our SED modelling indicates that optical flares with absent or weak corresponding γ -ray flares in epochs D and E could arise from changes in a combination of parameters, such as the bulk Lorentz factor, magnetic field, and electron energy density, or be due to changes in the location of the γ -ray-emitting regions.